The role of cyclin D1 and vascular endothelial growth factor (VEGF) in radiotherapy response of undifferentiated nasopharyngeal carcinoma - Nurhidayat, Ade Apon; Afiati, .; Usman, Hermin Aminah; Hernowo, Bethy Suryawathy (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Nasopharyngeal carcinoma (NPC) has a high incidence and mortality rate in SoutheastAsia included in Indonesia. Radioresistance is a major obstacle for a successful treatmentof NPC. DNA repair in the cell cycle and angiogenesis factors affect the response oftumor cells to radiotherapy. Cyclin D1 that functions in the cell cycle process and vascularendothelial growth factor (VEGF) as an angiogenesis factor are considered to play arole in the occurrence of radioresistance. The objective of this study was to evaluatethe association between cyclin D1 and VEGF expressions with radiotherapy responsein undifferentiated NPC. This study used a retrospective case control analysis design.Secondary data from medical records of patients diagnosed as undifferentiated NPC whoreceived a complete radiotherapy at the Department of Radiation Oncology, Dr. HasanSadikin General Hospital, Bandung. There were 44 samples divided into radiosensitive(22 samples) and radioresistant (22 samples) groups. Immunohistochemical examinationof cyclin D1 and VEGF expressions was performed on paraffin blocks of patients’nasopharyngeal biopsy. Data analysis used Chi-Square test with p ≤0.05. Cyclin D1 wasexpressed strongly in 86.4% of the radioresistant group and 59.1% in the radiosensitivegroup (p<0.05), VEGF was strongly expressed in 77.3% of the radioresistant group and54.5% in the radiosensitive group (p>0.05). In conclusion, there is significant associationbetween cyclin D1 expression with radiotherapy response in undifferentiated NPC.However, there is no association between VEGF expression with radiotherapy response.